The Difference of Motivation and Social Science Achievement with the Learning Application of STAD Video Media and STAD non-video - Robi’ul Setiawan (Jurnal Pendidikan Humaniora, 2014)
Perbedaan Motivasi dan Hasil Belajar IPS dengan Penerapan Pembelajaran STAD Bermedia Video dan STAD NonvideoAbstract: This study aimed to find: (1) differences in students’ motivation, among the group of stu-dents who are taught using STAD mediated video and non video in eighth grade social studies at SMP Negeri 3 Kare, (2) differences in student learning outcomes, between group of students who are taught using STAD mediated video and nonvideo in eighth grade social studies at SMP Negeri 3 Kare, and (3) the relationship between students ‘motivation with students’ learning outcomes. The use of quasi experiment research. Techniques of data analysis performed by t test. The results showed that: (1) there are significant differences between the motivation to learn the class A (STAD mediated video) with motivation to learn the class B (STAD nonvideo), (2) there are significant dif-ferences between the learning outcomes of class A (STAD mediated video) with the learning outcomes of the class B (STAD nonvideo), and (3) there is no significant relationship between students moti-vation with students learning outcomes.Key Words: learning motivation, learning outcomes, STAD mediated video Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) perbedaan motivasi belajar siswa antara ke-lompok siswa yang belajar dengan menggunakan pembelajaran STAD bermedia video dan STAD non video, (2) perbedaan hasil belajar siswa, antara kelompok siswa yang belajar dengan menggunakan pembelajaran STAD bermedia video dan STAD nonvideo, dan (3) hubungan antara motivasi belajar siswa dengan hasil belajar siswa. Penelitian ini menggunakan quasi eksperimen. Teknik analisis data dilakukan dengan uji t. Hasil penelitian menunjukkan bahwa: (1) terdapat perbedaan yang signifikan antara motivasi belajar kelas A (STAD bermedia video) dengan motivasi belajar kelas B (STAD non-video), (2) terdapat perbedaan yang signifikan antara hasil belajar kelas A (STAD bermedia video) dengan hasil belajar kelas B (STAD nonvideo), (3) tidak terdapat hubungan yang signifikan antara motivasi belajar siswa dengan hasil belajar siswa.Kata kunci: Motivasi belajar, hasil belajar, STAD bermedia video